8 weeks to SEALfit : a Navy SEAL's guide to unconventional training for physical and mental toughness - Divine, Mark (St. Martin's Griffin, 2014)
"To be SEALFit (tm) was developed by retired Navy SEAL Commander Mark Divine for the unique and specialized needs of professionals seeking to reach their fullest potential. To be SEALFit means you embody the character traits of discipline, drive, determination, self-mastery, honor, integrity, courage, and authentic leadership. We all share a need for our minds and bodies to work at peak performance over long periods of time, while maintaining an unconquerable spirit. The SEALFit athlete is different than the sport athlete. He or she demonstrates great endurance, the ability to train without equipment, be prepared for the known and the unknown, can display intense work capacity, are durable, mentally tough, and flourish as part of a team. These qualities allow strong individuals to thrive in life and lead by example. With 8 Weeks to SEALFit the athlete will: master the unbeatable mind get the best workout available with the least amount of equipment take a level-headed approach to nutrition develop exceptional overall functional strength, fitness, and mental toughness - the qualities that make a Navy SEAL Through teamwork, mental and physical preparation, and proper nutrition the SEALFIT athlete can cultivate the "Kokoro" (warrior) spirit, helping them be unbeatable in life. Join the thousands of other SEALFIT athletes that have improved their well-being through these tried and true methods presented by Commander Mark Divine"--